Maritime fuels of the future: What is the impact of alternative fuels on the optimal economic speed of large container vessels - Konstantinos Kouzelis; Koos Frouws; Edwin Van Hassel (Journal of Shipping and Trade (JST), 2022)
This study aims to determine the most appropriate alternative fuel technology to comply with possible different imposed emission regulations while ensuring optimal business performance. In this context, the most suitable alternative fuel technology minimizes the required freight rate while maximizing overall performance on technological, environmental, and other criteria. A decision support tool was developed combining the overall performance of alternative fuels based on technological, environmental, and other criteria via a simple multiattribute rating technique model with a financial model based on discounted cash flow analysis. In this model, also an optimization model is implemented to minimize the required freight rate by optimizing for economic vessel speed. This model provides quantified insights into the financial and operational effects of transitioning via either a 'market-based measure' regulatory scenario or an 'emission cap' scenario if current fuels do not reach the zero-emission targets in the future. Based on the analysis, it can be concluded that upgraded bio-oil, Fischer-Tropsch diesel and liquefied bio-methane can be considered the 'most promising' alternative maritime fuels of the future. Current fuels such as Heavy fuel oil and Liquified natural gas remain the 'most probable' to retain dominance without regulations. If there is a transition toward these alternative fuels, this will also lead to a shift toward lower sailing speeds.
Keywords: 650; Maritime industry; GHG reduction policies; Alternative fuels; Decision support tool; Economic speed optimization; Scenario analysis